1982
DOI: 10.3171/jns.1982.56.1.0026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the type of intracranial lesion on outcome from severe head injury

Abstract: ✓ Recent studies attempting to define the outcome from severe head injury have implied, directly or indirectly, that the severity of injury (as determined by the Glasgow Coma Scale (GSC)) is the sole determinant of outcome. Little attention has been focused on the type of lesion that causes the low GCS score, and there exists an unstated hypothesis that the lesion type is not an important determinant of outcome. No attempt has been made to determine whether patients who have the same GCS score caused by differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
176
2
40

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(227 citation statements)
references
References 6 publications
9
176
2
40
Order By: Relevance
“…Our study also found these three factors together have significant impact to the extent of 90% mortality. 18 Heissler et al found thickness of hematoma, midline shift are having significant impact on outcome. They found hematoma thickness of >10mm, with midline shift >5mm are having 30% increased mortality than those without.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found these three factors together have significant impact to the extent of 90% mortality. 18 Heissler et al found thickness of hematoma, midline shift are having significant impact on outcome. They found hematoma thickness of >10mm, with midline shift >5mm are having 30% increased mortality than those without.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors -Age, anisocoria, polytrauma, tomographic findings and ICH have been reported as factors independent from prognosis 12,[25][26][27][28][29][30] . In this study none of these factors was statistically correlated to prognosis (p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…É importante ressaltar que se tratava de um grupo homogêneo do ponto metabólico, com pacientes apresentando hematomas subdurais, extradurais, assim como lesões focais e inchaço cerebral isolado. O fato de um dos pacientes ter falecido, em razão de falência de múltiplos orgãos, dias após a última análise, em nada altera a assertiva de que todos os pacientes, mesmo aqueles com hematoma subdural, de pior prognóstico 9 , estavam dentro da categoria de boa evolução, no que se refere à lesão causal.…”
Section: Aspectos Clínicos E Metabólicos Dos Pacientes Estudadosunclassified
“…No que se refere ao metabolismo protéico-energético, Young et al 8 demonstraram que as proteínas de fase aguda tendem à normalização passadas duas semanas após o TCE. A influência do tipo da lesão intracraniana é comumente associada ao prognóstico do TCE , de forma que se estabeleceu para pacientes com escore de Glasgow entre 3 a 5 , uma taxa de mortalidade de 30% a 74% e, dependendo da lesão, boa recuperação entre 6% a 52% 9 .…”
unclassified